Multiregional analysis with use of regional accounts and Input-Output tables - Alexander Granberg; Ioulia Zaitseva (European Regional Science Association (ERSA), 2001)
Authors construct Regional input-output tables (11 products of goods and sevices) on the basis of regional accounts and National input-output table (120 products) by 79 subjects of the Russian Federation. Information of the Regional input-output tables is used for three types of multiregional models (size 79 x 11): a) multiregional input-output model; b) multiregional optimization model (with vector criterion function); c) spatially-economic equilibrium model. Multiregional economic analysis is developed by the following directions: 1) export-import impact on the regional economy; 2) possibilities of decreasing of regional trade deficit and deficit of regional balances of payment; 3) searching of equilibrium and quasi-equilibrium in the multiregional system; 4) possibilities of leveling of regions by the level of final consumption of households per capita; 5) use of reserves of the basic industrial capital in one regions for increase of final demand in another regions.
Keywords: 330